2019
DOI: 10.3855/jidc.10376
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of tigecycline and comparator agents against common pathogens: Indian experience

Abstract: Introduction: Tigecycline Evaluation and Surveillance Trail (TEST) study is an on-going global surveillance. The study was performed to determine the susceptibility of common pathogens to tigecycline and comparator antibiotics by broth microdilution (BMD) at two tertiary care centres in India from 2015 to 2017. Methodology: Total of 989 isolates collected from various clinical specimens between January 2015 and September 2017 from two centres in India were included. BMD was performed to determine the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the present study, in patients caused by MDR and polymicrobial infections, clinical success rate for tigecycline was significantly higher than that for meropenem at upon discharge visit, whereas there was no statistical difference. A surveillance trial about tigecycline against MDR Gram- (24). Another previously published systematic review and metaanalysis demonstrated that tigecycline combination therapy was associated with significantly lower 30-day mortality than does monotherapy (25).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in patients caused by MDR and polymicrobial infections, clinical success rate for tigecycline was significantly higher than that for meropenem at upon discharge visit, whereas there was no statistical difference. A surveillance trial about tigecycline against MDR Gram- (24). Another previously published systematic review and metaanalysis demonstrated that tigecycline combination therapy was associated with significantly lower 30-day mortality than does monotherapy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial susceptibility of all E. coli and K. pneumoniae isolates was determined by the Kirby-Bauer disk diffusion method on Cation-Adjusted Mueller Hinton agar (Merck, Germany) and interpreted as recommended by the Clinical and Laboratory Standards Institute (2018 CLSI breakpoints) or Food and Drug Administration (FDA) breakpoints guidelines (for tigecycline) [ 18 , 19 ]. Antibiotic discs used were as follow: penicillins [piperacillin (PIP, 100 μg)], β-lactam/β-lactamase inhibitor combinations [piperacillin/tazobactam (PTZ, 100/10 μg)], cephems [ceftazidime (CAZ, 30 μg), cefotaxime (CTX, 30 μg), cefepime (FEP, 30 μg), cefpodoxime (CPD, 30 μg)], monobactams [aztreonam (ATM, 30 μg)], carbapenems [imipenem (IPM, 10 μg), meropenem (MEM, 10 μg), ertapenem (ETP, 10 μg), doripenem (DOR, 10 μg)], aminoglicosides [gentamicin(GEN,10 μg)], Amikacin (AK, 30 μg)], Fluoroquinolones [ciprofloxacin (CIP, 5 μg)], inhibitors [trimethoprim-sulfamethoxazole (TS, 2.5 μg)], fosfomycins [fosfomycin/trometamol (FOT, 200 μg)], tigecycline (TGC, 15 μg), and nalidixic acid (NA, 30 μg), (Mast Group, Merseyside, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that tigecycline is a potential reserved drug owing to the growing drug resistance. 19…”
Section: Tigecycline—spectrum Of Activitymentioning
confidence: 99%
“…The authors concluded that tigecycline is a potential reserved drug owing to the growing drug resistance. 19 Tigecycline has been approved in the United States and Europe for the treatment of complicated skin and soft-tissue infections (cSSTI) and complicated intra-abdominal infections (cIAI) and additionally for community acquired bacteria pneumonia (CAP) in the United States. In India, tigecycline was approved for the same indications by the CDSCO in August 2006.…”
Section: Tigecycline-spectrum Of Activitymentioning
confidence: 99%